Clonal dynamics and somatic evolution of haematopoiesis in mouse - Chiraag D. Kapadia; Nicholas Williams; Kevin J. Dawson; Caroline Watson; Matthew J. Yousefzadeh; Duy Le; Kudzai Nyamondo; Sreeya Kodavali; Alex Cagan; Sarah Waldvogel; Xiaoyan Zhang; Josephine De La Fuente; et al. (Nature, 2025)
Abstract Haematopoietic stem cells maintain blood production throughout life 1 . Although extensively characterized using the laboratory mouse, little is known about clonal selection and population dynamics of the haematopoietic stem cell pool during murine ageing. We isolated stem cells and progenitors from young and old mice, identifying 221,890 somatic mutations genome-wide in 1,845 single-cell-derived colonies. Mouse stem cells and progenitors accrue approximately 45 somatic mutations per year, a rate only approximately threefold greater than human progenitors despite the vastly different organismal sizes and lifespans. Phylogenetic patterns show that stem and multipotent progenitor cell pools are established during embryogenesis, after which they independently self-renew in parallel over life, evenly contributing to differentiated progenitors and peripheral blood. The stem cell pool grows steadily over the mouse lifespan to about 70,000 cells, self-renewing about every 6 weeks. Aged mice did not display the profound loss of clonal diversity characteristic of human haematopoietic ageing. However, targeted sequencing showed small, expanded clones in the context of murine ageing, which were larger and more numerous following haematological perturbations, exhibiting a selection landscape similar to humans. Our data illustrate both conserved features of population dynamics of blood and distinct patterns of age-associated somatic evolution in the short-lived mouse.